Sensitivity analysis of HEC-RAS model / Mastijah Ali - Ali, Mastijah (2005)
Recently, the number of researches who interested in water resources knowledge shows an increment such as in water supply, irrigation, flood mitigation and water quality control. Science and technology are applied in their research for the reason of economical and efficient design, operation and maintenance in various projects. Development in computer technology and numerical methods of solution has lead to the rising interest in applying the modeling for surface water hydrology. The difficulty to get the hydrologic data and shortage of its record is the main factors, which encourage researchers to use the numerical models as a device in flood studies. In the present study, numerous programs are available to solved flooding problems such as HEC-RAS, MIKE 11, ISIS and DIVAST. In this research, River Analysis System program, which was developed by the Hydrologic Engineering Center (HEC-RAS), are used in order to verify the capability of HEC-RAS to quantify flood level problems under various hydraulics conditions. This was done using sensitivity analysis of the HEC-RAS model based on four parameters selected. Parameter that is being tested was the bed slope of the channel, storm period, peak discharge and Manning’s coefficient. The study tried to simulate the behavior of the flow when changes are made in the parameter of the idealized channel. Simulation procedures were done through unsteady flow analysis of idealized channel in the idealized condition in a mean to evaluate the effect of uncertainties in the flow.